A new approach to controller design for networked control systems with multiple-packet transmissions. (25th April 2011) - Yu, Junyan; Wang, Long; Yu, Mei
Stabilisation and robust stabilisation problems of Networked Control Systems (NCSs) with multiple-packet transmissions are addressed. We focus our attention on the case that the packets are transmitted over token-passing bus networks, and model the systems as periodically switched systems based on the exact network timing property. Furthermore, by using Elimination lemma, we present stabilising conditions which provide less conservative evaluation for stabilising domains, as well as a novel design method for state feedback controllers. Several numerical examples and simulations are worked out to demonstrate the effectiveness of the proposed design technique.